ISLAM I EVROPSKA UNIJA: AUSTRIJSKI MODEL - Schmied, Martina; Wieshaider, Wolfgang; Seferović, Samira (Novi Muallim, 2005)
U djelu Islam and European Union, ur. Richard Potz & Wolfgang Wieshaider, PETERS, Leuven- Paris- Ddley, MA, 2004. Prijevod s engleskog: Samira Seferović